Penguasaan Tanah oleh Negara Perspektif Hukum Positif dan Hukum Islam - Suyadi, Yagus; Rafsanzani, Risahlan (Al-Mazaahib: Jurnal Perbandingan Hukum, 2023)
The government, as the administrator of the state, is obligated to fulfill the welfare of the broader society. To fulfill this task, the state has rights and obligations regarding land management within its territory. In practice, there are many lands that are not managed by their owners (citizens). Can the state take over the ownership of those lands for the purpose of promoting the welfare of the wider society? This article seeks to answer how the law allows the state to take ownership of lands based on the perspective of the Basic Agrarian Law (UUPA) and Islamic Land Law. This article is a literature review based on the study and analysis of available legal sources in the form of written materials such as books, journals, and legislative documents. The article adopts a statutory approach to understand and interpret the applicable legal regulations. The findings of this article suggest that both the state law stated in UUPA and Islamic law based on the opinions of scholars grant the government/state the right and obligation to manage the lands. According to Government Regulation (PP) No. 20 of 2021, the government is authorized to take over abandoned lands. Similarly, in Islamic law, based on the opinion of Umar that has reached a consensus (ijma'), lands abandoned by their owners for a period of three years can be taken over by the government/state. This means that both positive law and Islamic law sanction the acquisition of abandoned lands for the purpose of proper government management and utilization for the public prosperity.[Pemerintah sebagai pengelola negara diwajibkan untuk memenuhi kesejahteraan masyarakat luas. Untuk memenuhi tugas tersebut, negara memiliki hak dan kewajiban atas pengelolaan tanah yang berada dalam wilayahnya. Pada faktanya, banyak tanah yang tidak dikelola oleh pemiliknya (warga negara). Apakah tanah tersebut dapat diambil alih kepemilikannya oleh negara dalam rangka pemenuhan kesejahteraan masyarakat yang lebih luas? artikel ini berusaha menjawab bagaimana hukum pnegambilan hak tanah terlantar oleh negeara berdasarkan perspektif (UUPA) dan Hukum Pertanahan dalam Islam. Artikel ini merupakan penelitian pustaka yang didasarkan pada studi dan analisis terhadap sumber-sumber hukum yang tersedia dalam bentuk tulisan, seperti buku, jurnal, atau dokumen perundang-undangan. Artikel ini menggunakan pendekatan undang-undang untuk memahami dan menginterpretasi peraturan-peraturan hukum yang berlaku. Artikel ini meneukan bahwa baik hukum negara yang tercantum dalam UUPA dan hukum Islam yang bersumber dari pendapat ulama, sama-sama memberikan hak dan kewajiban kepada pemerintah/negara untuk mengelola tanah. Berdasarkan Peraturan Pemerintah (PP) No 20 Tahun 2021, pemerintah dapat mengambil alih tanah yang ditelantarkan oleh pemiliknya. Adapun dalam hukum Islam, berdasarkan pendapat Umar yang menjadi ijma’, tanah yang ditelantarkan pemiliknya dalam kurun waktu 3 tahun dapat diambil alih oleh pemerintah/negara. Artinya, baik hukum positif maupun hukum Islam sama-sama mengesahkan pengambilan aset tanah yang ditelantarkan oleh pemiliknya. Tujuannya sama, agar tanah yang ditelantarkan tersebut dapat dikelola oleh pemerintah dan hasilnya dapat digunakan untuk kesejahteraan umum.]